Sprayable Hydrogel for pH-Responsive Nanozyme-Derived Bacteria-Infected Wound Healing - Chao, Furong; Cao, Chengliang; Xu, Yin; Gu, Yunjie; Qu, Xinyu; Wang, Qian; Qu, Lu−Lu; Guo, Yuxin; Dong, Xiaochen (ACS applied materials & interfaces, 2025)
Long-term inflammation and persistent bacterial infection are primary contributors to unhealed chronic wounds. The use of conventional antibiotics often leads to bacteria drug resistance, diminishing wound healing effectiveness. Nanozymes have become a promising alternative to antimicrobial materials due to their low cost, easy synthesis, and good stability. Herein, we develop a novel sprayable hydrogel based on carboxymethyl chitosan (CMCS) and oxidized hyaluronic acid (OHA), incorporating Au nanoparticle-carbon nitride (AuNPs-C3N4) nanozyme, glucose, and Mn2+ for bacteria-infected wound healing. The hydrogel forms rapidly in situ upon spraying and gradually degrades on the wound area, releasing the AuNPs-C3N4 nanozyme, which exhibits robust glucose oxidase-like (GOx-like) activity, initiating a comprehensive catalytic cascade through a Mn2+-mediated Fenton-like reaction that generates hydroxyl radicals (•OH) to eliminate Staphylococcus aureus (S. aureus) and Methicillin-resistant S. aureus (MRSA). Computational results indicate that interactions between AuNPs and g-C3N4 maximize their synergistic effects in a heterojunction, improving O2 adsorption and facilitating electron-O2 interactions to optimize catalytic activity. Further experiments demonstrate that the hydrogel can rapidly cover wounds in situ, while CMCS promotes collagen production and fibroblast proliferation, offering a viable strategy for the healing of bacteria-infected wounds.